The Effectiveness of Rice Washing Waste on the Growth of Stem Height and Leaf Width of Green Spinach Plants (Amaranthus hybridus L.) - Veronika Amelia Simbolon; Annisa Pratiwi Putri; Hendra Dermawan Sitanggang; Iza Lianti (Humanistic Network for Science and Technology (HNST), 2022)
Rice washing waste can cause pollution if not treated, the waste can be used as liquid organic fertilizer. The fertilizer contains the nutrients needed by plants and is environmentally friendly. The purpose of the study was to determine the effectiveness of rice washing waste on the growth of stem height and leaf width of green spinach plants. This research was an experimental study with a factorial design. The factorial pattern was 2 x 3 with 3 repetitions. The first factor was rice washing waste and the second factor was variations in the concentration of liquid fertilizer. Variations in the concentration of liquid organic fertilizer from rice washing waste were 50%, 75% and 100%. The sample of this study was 100 stems of green spinach plants. Post hoc test found that the most effective concentration of liquid organic fertilizer on green spinach plant height was 50% (fermented) and 75% (without fermentation), while the leaf width concentration was 75%. There was no effect of giving liquid organic fertilizer from rice washing waste to the number of green spinach leaves. There was an effect of giving organic fertilizer from rice washing waste on stem height and leaf width of green spinach plantsKeywords: liquid organic fertilizer; rice washing waste; green spinach plant